The scarlet ribbon [large type] - Stephens, Naomi (Center Point Large Print, 2025)
"As the Revolutionary War unfurls around her, Rebekah Stanton is abandoned by the man who once claimed to love her. Shunned by her father and forced to give up her child, she finds herself thrust into prostitution at the local boardinghouse. When the British seize control of the nearby fort, she gives little thought to the officers who frequent the boardinghouse. Men are men regardless of the color of their uniform . . . or so she believes. But then a young man-a Patriot spy named Benjamin Renshaw-stumbles upon her in the darkness, and she saves him from a group of pursuing Redcoats. With an attack on the fort brewing in the background and the father of her child returned to serve with the British, Rebekah is torn between old dreams and new hope, struggling all the while to find peace and forgiveness in a place of rising conflict."--